Delayed clearance of monkeypox virus in a patient with co infection with secondary syphilis - Opardija, Almira; Sivasubramanian, Geetha (IDCases, 2023)
Several studies from the current 2022 monkeypox (MPX) outbreak have documented co-infections with sexually transmitted infections (STIs), such as gonorrhea, chlamydia, and syphilis. We present a patient with MPX and secondary syphilis who failed to clear the MPX virus 30 days after illness onset despite a 14-day course of tecovirimat therapy.